2015
DOI: 10.1371/journal.pone.0143081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Utility of Whole Genome Sequencing of Measles Virus in the Characterisation of Outbreaks

Abstract: BackgroundMeasles is a highly infectious disease caused by measles virus (MeV). Despite the availability of a safe and cost-effective vaccine, measles is one of the world-leading causes of death in young children. Within Europe, there is a target for eliminating endemic measles in 2015, with molecular epidemiology required on 80% of cases for inclusion/exclusion of outbreak transmission chains. Currently, MeV is genotyped on the basis of a 450 nucleotide region of the nucleoprotein gene (N-450) and the hemaggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…SAMtools v1.4 was used to compute the percent reads mapped and coverage depth (34). Mapping consensuses for Illumina sequencing were generated using QuasiBam (40). Maximum likelihood phylogeny was generated for the HA gene segment using RAxML v8.2.10 (41), in which a general time-reversible model of nucleotide substitution and a gamma-distributed rate variation among sites were applied.…”
Section: Methodsmentioning
confidence: 99%
“…SAMtools v1.4 was used to compute the percent reads mapped and coverage depth (34). Mapping consensuses for Illumina sequencing were generated using QuasiBam (40). Maximum likelihood phylogeny was generated for the HA gene segment using RAxML v8.2.10 (41), in which a general time-reversible model of nucleotide substitution and a gamma-distributed rate variation among sites were applied.…”
Section: Methodsmentioning
confidence: 99%
“…Logically, however, it may be beneficial to plan strategically for entire genome sequencing, to allow detailed monitoring of any ongoing PPRV epidemic. This genome-wide approach was shown recently to be essential for identifying the origin of a measles outbreak at the 2010 Vancouver Winter Olympic Games [76][77][78]; furthermore, full PPRV genome sequences, including vaccine sequences, are already available to support this effort [79,80] (Table 1 and Fig. 2).…”
Section: Novel Tools In the Pipelinementioning
confidence: 99%
“…Our results suggest that the general population sero -immunity among children between 9 to 59 months as in 2014, was 83.0%, well below the acceptable herd immunity threshold (93-95%) necessary to interrupt measles transmission as suggested by several studies [14,19,32]. Comparatively, this is much higher than what another recent (2011) study in Bangui, Central African Republic (CAR) found (57.3 %) on a research conducted in 2008 despite having reached immunization coverage's of more than 90% in 2006 [34].…”
Section: Discussionmentioning
confidence: 44%
“…Such association has been emphasized by world health organization [19,36,37]. And mentioned in reports from other studies as well [14,20,38]. The odds of being seronegative were higher for residents of Narok County as compared to Kwale or Lamu counties.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation